Buchwald coupling of quinoxaline-o-sulfonates leading to the heterocyclic compounds with potential medicinal properties against TB - Ramakadi, Tselane Geneva (University of Limpopo, 2018)
The dissertation describes the use of 2-benzenesulfonyloxyquinoxaline as a good coupling partner for different amine substrates. The palladium-mediated cross- coupling of aryl electrophiles and amines has become a widely used method of constructing arylamine frameworks. The formation of carbon-nitrogen bonds was accomplished via palladium-catalysed Buchwald-Hartwig amination employing different amine substrates to yield substituted quinoxaline-2-amines compounds in good to moderate yields. Buchwald ligands (Xphos, tButylxphos and BrettPhos), were varied with different amine substrates in an attempt of improving the yields. Compounds 81a N-phenylquinoxalin-2-amine and 82b, N-benzylquinoxalin-2-amine were obtained with the yield over 70 % employing Xphos as the ligand. Significant attention has also been given to the application of cross coupling reaction protocols in substrates bearing electron withdrawing substituents. The presence of deactivating groups on the arylamine such as fluoro, nitro and iodo proved to be a challenge as only few compounds were synthesised in moderate yields. Compound 81b, N-(4-fluorophenyl)quinoxalin-2-amine which has electronegative atom attached, showed significant improvement when employing tButyl-Xphos ligand rather than XPhos since the yield improved from 10 % to 71 %. Furthermore, nucleophilic substitution on Buchwald-Hartwig coupled compounds by treating them with alkyl iodides was successful when using methyl and ethyl electrophiles on the N-H group of 81a 2-quinoxalineamine. The synthesised quinoxaline derivatives comprised 7 novel compounds. The in vitro analysis on anti-tubercular screening against H37RvMA strains of Mycobacterium tuberculosis was conducted on 9 compounds. The results revealed none of the compounds to have promising inhibition percentages against Mycobacterium tuberculosis when compared with rifampicin which was used as a positive control. Screening against malaria with chloroquine as the control also did not yield any active compounds.
Thesis (M. Sc. (Chemistry)) --University of Limpopo, 2018
Keywords: Angular momentum (Nuclear physics)|xCoupling and recoupling; Coupling constants